Functional Supramolecular Polymers: A Fluorescent Microfibrous Network in a Supramolecular Hydrogel for High‐Contrast Live Cell‐Material Imaging in 3D Environments. Issue 18 (8th July 2016) - Hsu, Shu‐Min; Wu, Fang‐Yi; Cheng, Hsun; Huang, Yu‐Tang; Hsieh, Yi‐Ru; Tseng, Dion Tzu‐Huan; Yeh, Mei‐Yu; Hung, Shih‐Chieh; Lin, Hsin‐Chieh
Abstract : A new bottom‐up strategy based on aromatic peptide amphiphile is developed for a high‐contrast visualization of 3D live cell‐material imaging—something that has been difficult to achieve previously because of the problems associated with the diffraction of light by the nanosized peptide materials and the aggregation‐caused quenching of aggregated π‐conjugated fluorophores in the nanostructures. This study reports an example of a novel supramolecular hydrogelator, naphthaleneimide‐phenylalanine (NI‐Phe), which forms a self‐supporting hydrogel displaying a unique microfibrous network and promising aggregation‐induced emission characteristics at pH 7.4. The storage modulus of the NI‐Phe gel supports the mass of a cell for 3D cell culturing. This work illustrates a new dopant‐free supramolecular approach, complementary to well‐established doping procedures that should facilitate the development of live cell imaging in 3D scaffolding materials. Abstract : A fluorescent peptide amphiphile based on a naphthaleneimide–phenylalanine residue which forms a self‐supporting hydrogel displaying a unique microfibrous network and promising aggregation‐induced emission characteristics at pH 7.4 for a high‐contrast 3D live cell‐scaffold imaging is developed.